Adaptación de una cepa compatible con Acidithiobacillus ferrooxidans sobre concentrados de calcopirita (CuFeS2), esfalerita (ZnS) y galena (PbS) (2011)
ABSTRACT: In this study the adaptation of Acidithiobacillus ferrooxidans-like to high concentrations of chalcopyrite, sphalerite and galena were evaluated with two mineral-particle sizes: 200 and 325 Tyler mesh. The strain was adapted using two simultaneous processes. The first one consisted in a gradual decreasing of the main energy source, ferrous sulphate. The second one consisted in a gradual increasing of the mineral content. Finally, a test was made without ferrous sulphate. The serial subculturing was found to be an efficient strategy to adapt Acidithiobacillus ferrooxidans-like to higher concentrations of chalcopyrite, sphalerite and galena. This indicates that a suitable protocol was employed. The results showed that Acidithiobacillus ferrooxidans-like is more resistant to high concentration of sphalerite, chalcopyrite and galena in descendant order. The particle size played an important role in the adaption of microorganism to the mineral.